Impact of lactic acidosis on the survival of lewis lung carcinoma cells - Kolesnik, D.L.; Pyaskovskaya, O.N.; Solyanik, G.I. (Experimental Oncology, 2017)
Aim: To investigate the effect of lactic acidosis on the survival of Lewis lung carcinoma cells under glucose-deprived conditions. Materials and Methods: LLC/R9 variant of Lewis lung carcinoma cells was cultured in glucose deficit or complete culture medium. Conditions of lactic acidosis, lactosis, and acidosis were generated in glucose deficit medium. Cell survival, cell cycle, apoptosis, autophagy, and the content of glucose, lactate, vascular endothelial growth factor in the culture medium were determined. Light and fluorescent microscopy, flow cytometry, spectrophotometry, and ELISA were used. Results: It has been found that 24 h incubation of tumor cells under lactic acidosis caused (i) the reduction of the number of living cells by 33% (p < 0.05) and 56% (p < 0.05); (ii) the inhibition of apoptosis by 4.3-fold (p < 0.05) and 3.3-fold (p < 0.05); (iii) the reduction of the rate of glucose consumption by 2-fold (p < 0.05) and 2.5-fold (p < 0.05); (iv) an increase of lactate production more than twice (p < 0.05) and 1.6-fold (p < 0.05) compared with these indexes under conditions of glucose deficiency or complete glucose-containing medium, respectively. However, on the second day of culture under lactic acidosis, the number of viable cells reached a maximum, in contrast to culture in the complete medium. The number of live cells on the seventh day of culture under lactic acidosis exceeded almost 2–3 times (p < 0.05) that in the culture under conditions of the glucose deprivation or in complete medium. On the third day under lactic acidosis the autophagolysosomes count was 54% (p < 0.05) lower that that under glucose deficit. Conclusions: Lactic acidosis promoted the survival and proliferation of Lewis lung carcinoma cells by energy system reprogramming directed on inhibition of apoptosis and autophagy, a significant decrease in the rate of glucose utilization and activation of glutaminolysis and, consequently, increase of the lactate production rate. Inhibition of lactate production by tumor cells may be considered as a promising approach for more efficient antiangiogenic treatment of cancer.